Exclusion and discrimination of the LGBTTTIQ+ community, in the labor market of Tonalá, Chiapas - Esponda-Pérez, Jorge Alberto; Marroquín Figueroa, Julia María; Galindo Ramírez, Sergio Mario; Zea Gordillo, Reyna Esperanza (Eximia, 2023)
Tonalá is a coastal municipality of Chiapas, with approximately 90,000 inhabitants, in which 49% are men and 51% women, recognized for its different business, commercial, restaurant and hotel activities, with conservative traditions, where people with different sexual attractions and inclinations known as the community (LGBTTTIQ+), are victims of discrimination, verbal and psychological aggression in the workplace. The main objective of this research is to determine the different problems that professionals have faced from the different work areas, hindering their standard of living, causing them moral damages due to the rejection they have faced. Generating the question: What level of exclusion and discrimination have they faced in the labor market for belonging to this community in the municipality of Tonalá? A case study was carried out in the local labor market, to graduates with an educational level of Bachelor’s degree and who have or have had a formal job, all members of this community, based on structured interviews, in order to obtain direct and Detailed based on your work experience. The results have been surprising, since there is marked discrimination among professionals, from the moment they seek to enter the labor market and during development, since there are difficulties between acceptance of people with sexual diversity and respect for human rights and labor.